Usable Social Science - Smelser, Neil J.; Reed, John S. (John Shepard), 1939- (Book collections on Project MUSE., 2012)
"This volume is a one-of-a-kind contribution to applied social science and the product of a long collaboration between an established, interdisciplinary sociologist and a successful banking executive. Together, Neil Smelser and John Reed use a straightforward approach to presenting substantive social science knowledge and indicate its relevance and applicability to decision-making, problem-solving and policy-making. Among the areas presented are space-and-time coordinates of social life; cognition and bias; group and network effects; the role of sanctions; organizational dynamics; and macro-changes associated with economic development. Finally, the authors look at the big picture of why society at large demands and needs social-science knowledge, and how the academy actually supplies relevant knowledge."--